RIPTE: Runtime Integrity Protection Based on Trusted Execution for IoT Device. (23rd September 2020) - Qin, Yu; Liu, Jingbin; Zhao, Shijun; Feng, Dengguo; Feng, Wei
Abstract : Software attacks like worm, botnet, and DDoS are the increasingly serious problems in IoT, which had caused large-scale cyber attack and even breakdown of important information infrastructure. Software measurement and attestation are general methods to detect software integrity and their executing states in IoT. However, they cannot resist TOCTOU attack due to their static features and seldom verify correctness of control flow integrity. In this paper, we propose a novel and practical scheme for software trusted execution based on lightweight trust. Our scheme RIPTE combines dynamic measurement and control flow integrity with PUF device binding key. Through encrypting return address of program function by PUF key, RIPTE can protect software integrity at runtime on IoT device, enabling to prevent the code reuse attacks. The results of our prototype's experiment show that it only increases a small size TCB and has a tiny overhead in IoT devices under the constraint on function calling. In sum, RIPTE is secure and efficient in IoT device protection at runtime.